EVALUATION OF TEACHER READINESS USING THE CIPP MODEL IN LIMITED FACE-TO-FACE LEARNING - helda oktarina; Jasiah Jasiah; Setria Utama Rizal (EduHumaniora | Jurnal Pendidikan Dasar Kampus Cibiru, 2022)
This study is to describe the readiness of teachers in Limited Face-to-face Learning (PTMT) during the COVID-19 pandemic in the 2021 academic year. This is motivated by the importance of teacher readiness in dealing with the Covid-19 pandemic, namely by implementing Limited Face-to-face Learning (PTMT). in the teaching and learning process. This study uses a method with a qualitative approach to the type of evaluation research using the CIPP model. The subjects of this study were two PAI subject teachers and Budi Pekerti. The results of this study indicate that teacher readiness is viewed from the four components in the CIPP model as follows; 1) the context component of teacher readiness in learning planning that the teacher downloads the lesson plans and syllabus from the internet. The learning objectives are not formulated based on the ABCD formula. Learning activities follow the lesson plans from the internet and there is no assessment in the lesson plans. LKPD uses multiple choice daily test sheets. Instructional media using the blackboard 2) The input component of teacher readiness in learning in terms of methods using lectures, questions and answers and assignments. The material aspect is taken in the student book. 3) The components of the learning process process, there are several activities that have not been carried out, such as the preliminary activities the teacher does not convey the learning objectives, in the core activities many learning steps are not carried out and in the closing activities the teacher does not conduct an assessment. 4) The product component of student learning outcomes is seen from the affective, cognitive and psychomotor aspects.